Survey on key technologies of covert channel in ubiquitous network environment - Fenghua LI; Chaoyang LI; Chao GUO; Zifu LI; Liang FANG; Yunchuan GUO (Tongxin xuebao)
In the ubiquitous network environment, covert channel bypasses the system’s security strategy to transmit covert information by modifying the system’s shared resources, which poses a serious security threat to the computer and network system.The researches on covert channel in ubiquitous network environment were summarized and analyzed from three aspects of measurement, construction and detection.First, the typical covert channel metrics including the capacity, robustness, anti-detection, regularity and shape were summarized.Second, the construction technologies of covert channel were summarized and analyzed from six aspects of resource sharing, capacity, robustness, anti-detection, advantages and disadvantages in the first time.Third, the detection technologies of covert channel were compared and analyzed from five aspects of the type of covert channel, accuracy, whether it can be blind detection, the advantages and disadvantages.Finally, the development trends of covert channel were summarized and future research directions were prospected.